Mechanistic and experimental study of VxCy nitridation in N2 atmosphere to prepare high-quality vanadium nitride - Li Liu; Bo Liu; Xiumin Chen; Wei Liu; Jie Zhou; Xiran Zhao; Lianfeng Yang; Zhuo Sheng; Bin Yang; Baoqiang Xu; Dachun Liu; Wenlong Jiang (Journal of Materials Research and Technology, 2024)
Vanadium nitride (VN) serves as a versatile material in various applications such as electrodes, ceramics, catalysts, and alloy components owing to its robust electrical performance, favorable stability, and high hardness. However, conventional VN synthesis methods require long soaking times and high temperatures. This study investigates a method wherein VxCy powder was soaked in an N2 atmosphere for a shorter period of time at a lower temperature to produce high-quality VN particles. The mechanism underlying this process was investigated via thermodynamic analyses, ab initio molecular dynamics (AIMD) simulations, and experimental studies. Thermodynamic analysis validates the thermodynamic feasibility of the reactions between VxCy and N2 to produce VN, while the atomic-level interactions between VxCy, N2, and surplus C atoms were comprehensively elucidated. By analyzing the two systems, it was discovered that the surplus C promoted the combination of N2 molecules with V atoms to form V–N in shorter AIMD simulation durations. Surplus C increased the chance of N2 molecules and V atoms to contact, similar to a catalytic effect, by activating N2 molecules to decompose and further reacted with V atoms to form VN. According to the experimental results, high-quality VN particles were formed at a heating temperature of 1323 K and soaking period of 90 min. Field-emission scanning electron microscopy (SEM) coupled with energy-dispersive spectrometry (EDS), particle size distribution analysis, and X-ray diffraction (XRD) were used to characterize the final product. The O and N contents were measured by an O/N analyzer at 0.11% and 17.4%, respectively. Accordingly, a C/S analyzer measured the C content at 3.92%. These analyses indicate that high-quality VN can be obtained by the VxCy nitridation in N2 atmosphere.